Begonia tuanii (sect. Platycentrum, Begoniaceae), a new species from Lao Cai Province, North Vietnam - Hoang, Thanh Son; Lin, Che-Wei (Phytotaxa, 2022)
Begonia tuanii from Lao Cai Province of Vietnam is described and illustrated. The habit of B. tuanii is mostly similar with B. fordii, but it can be distinguished by its bracts glabrous (vs. pilose) abaxial surface, larger outer tepals of staminate flower by 25–40 × 24–35 mm (vs. 6–8 × 5–77 mm) that are whole glabrous (vs. abaxially hairy), inner ones 20–35 × 10–20 mm (vs. 5.6–7.5 × 3–4 mm) and glabrous (vs. pilose) ovary. Referring to the IUCN of Nature criteria, B. tuanii is proposed to be Endangered (EN D).